Evaluation of 2‐Thiothiazolidine‐4‐Carboxylic Acid, a Common Metabolite of Isothiocyanates, as a Potential Biomarker of Cruciferous Vegetable Intake. Issue 3 (22nd November 2018) - Palliyaguru, Dushani L.; Salvatore, Sonia R.; Schopfer, Francisco J.; Cheng, Xuemei; Zhou, Jingyang; Kensler, Thomas W.; Wendell, Stacy G.
Abstract : Scope: Cruciferous vegetable consumption is associated with favorable health outcomes. Bioactive compounds arising in these, especially isothiocyanates, exert effects that contribute to prevention of disease, in large part through the attenuation of inflammation and oxidative stress. However, much about isothiocyanate metabolites and their role as biomarkers of crucifer intake remain unknown. Methods and results: The utility and limitations of 2‐thiothiazolidine‐4‐carboxylic acid (TTCA) as a urinary biomarker of broccoli beverage intake are tested in a randomized crossover clinical trial where 50 participants consumed either a glucoraphanin‐rich (GRR) or sulforaphane‐rich (SFR) beverage. Compared to run‐in and wash‐out periods, significantly higher urinary TTCA is observed after broccoli beverage consumption. Measurements also show that TTCA is present in beverage powders and in all tested cruciferous vegetables. GRR results in excretion of ≈87% of the ingested TTCA while SFR results in excretion of ≈176%. Elevated urinary TTCA is observed in rats administered 100 µmol kg –1 SFN. Unlike SFN, TTCA does not activate Nrf2‐mediated cytoprotective signaling. Conclusion: Collectively, TTCA appears to be a common isothiocyanate‐derived metabolite that has the capacity to be utilized as a biomarker of cruciferous vegetables that would be beneficial for objective and quantitative tracking of intake in studies. Abstract : Studying the health effects of cruciferous vegetables is limited by the absence of a reliable biomarker that can accurately determine intake levels. 2‐Thiothiazolidine‐4‐carboxylic acid (TTCA) is formed during isothiocyanate metabolism in cruciferous plants. Urinary levels of TTCA can therefore likely predict intake of all types of cruciferous vegetables, irrespective of the identity of the precursor glucosinolate species. With further validation in large nutritional epidemiology studies, TTCA may be a useful biomarker to assess intake of crucifers.